PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERBANKAN - Pertiwi, Nugraheni Restu; Yusuf, Muhammad (PRESTASI, 2013)
AbstractÂ Â Â Â The purpose of this study is to investigate the relation between Intellectual Capital with financial banks perfomance. Measurement of Intellectual Capital uses VAICâ¢, while measurement of financial banks perfomance used CAMELS (CAR, NPL, PDN, ROA, LDR and MR). The population of the study is the listed banks on Indonesia Stock Exchange period 2007 until 2011. Determination of the sample in this study is carried out by using the method of purposive sampling. The hypotheses are tested using Partial Least Square analysis. The result show that Intellectual Capital is positive influential to financial banks perfomance with CAR, ROA, and MR, negative influential to financial banks perfomance with NPL and MR, and not influential to financial banks perfomance with PDN. Â Keywords: Intellectual Capital, VAICâ¢, financial banks perfomance, CAMELS (CAR, NPL, PDN, ROA, LDR, and MR), Partial Least Square (PLS)